2012
DOI: 10.1021/ja306519h
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibition of c-MYC:MAX Leucine Zipper Formation Is Revealed by Ion Mobility Mass Spectrometry

Abstract: The leucine zipper interaction between MAX and c-MYC has been studied using mass spectrometry and drift time ion mobility mass spectrometry (DT IM-MS) in addition to circular dichroism spectroscopy. Peptides comprising the leucine zipper sequence with (c-MYC-Zip residues 402-434) and without a postulated small-molecule binding region (c-MYC-ZipΔDT residues 406-434) have been synthesized, along with the corresponding MAX leucine zipper (MAX-Zip residues 74-102). c-MYC-Zip:MAX-Zip complexes are observed both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…However, many of the active species belong to structural classes annotated as nonselective ligands in pharmaceutical screening libraries, so-called pan-assay interference compounds (PAINS) (Baell and Holloway 2010;Whitty 2011), establishing important first directions for follow-up chemistry. Perhaps consistent with this behavior, incisive and important studies have observed multiple binding events of bioactive compounds along the MYC protein by circular dichroism (Hammoudeh et al 2009), nuclear magnetic resonance (NMR) (Hammoudeh et al 2009), and most recently by mass spectrometry (Harvey et al 2012). The relatively low potency, demonstrable selectivity, and durable biostability of lead compounds have prevented use in MYC model systems in vivo (Guo et al 2009;Clausen et al 2010), but insights are emerging from this work and structural modeling.…”
Section: Toward Direct Inhibition Of Mycmentioning
confidence: 77%
“…However, many of the active species belong to structural classes annotated as nonselective ligands in pharmaceutical screening libraries, so-called pan-assay interference compounds (PAINS) (Baell and Holloway 2010;Whitty 2011), establishing important first directions for follow-up chemistry. Perhaps consistent with this behavior, incisive and important studies have observed multiple binding events of bioactive compounds along the MYC protein by circular dichroism (Hammoudeh et al 2009), nuclear magnetic resonance (NMR) (Hammoudeh et al 2009), and most recently by mass spectrometry (Harvey et al 2012). The relatively low potency, demonstrable selectivity, and durable biostability of lead compounds have prevented use in MYC model systems in vivo (Guo et al 2009;Clausen et al 2010), but insights are emerging from this work and structural modeling.…”
Section: Toward Direct Inhibition Of Mycmentioning
confidence: 77%
“…Its activity is dependent on heterodimerisation with the disordered protein Max (Blackwood and Eisenman 1991). Both c-Myc and Max are highly disordered in their free forms and undergo mutual coupled binding and folding to form the heterodimer complex via a basic helix-loop-helix leucine zipper domain present in both proteins (Hammoudeh et al 2009;Harvey et al 2012;Michel and Cuchillo 2012). This interaction has been reported to be druggable by small molecules that bind to the monomeric and disordered c-Myc (Hammoudeh et al 2009;Harvey et al 2012;Michel and Cuchillo 2012).…”
Section: Case Study 2 Targeting the C-myc-max Interactionmentioning
confidence: 99%
“…Both c-Myc and Max are highly disordered in their free forms and undergo mutual coupled binding and folding to form the heterodimer complex via a basic helix-loop-helix leucine zipper domain present in both proteins (Hammoudeh et al 2009;Harvey et al 2012;Michel and Cuchillo 2012). This interaction has been reported to be druggable by small molecules that bind to the monomeric and disordered c-Myc (Hammoudeh et al 2009;Harvey et al 2012;Michel and Cuchillo 2012). NMR spectroscopy revealed that these molecules bind to a disordered site in the c-Myc monomer located at the interface between the helix-loop-helix and leucine zipper in the c-Myc-Max complex (Hammoudeh et al 2009).…”
Section: Case Study 2 Targeting the C-myc-max Interactionmentioning
confidence: 99%
“…Modulation of protein conformation by a weak binding ligand has previously been shown by IMMS (Harvey et al, 2012). Interestingly, IMMS can detect the changes in p53 conformation induced by single point mutations in the p53 core domain .…”
Section: Discussionmentioning
confidence: 85%
“…IMMS is an attractive addition to native mass spectrometry as it allows study of the topology of proteins under various conditions (Jurneczko et al 2013;Harvey et al 2012). We performed IMMS analysis of both wt and The mass spectra for Np53 without RITA, with RITA and the control spectra show no mass .…”
Section: Critical Role Of Serine 33 and Serine 37 For Rita/p53 Interamentioning
confidence: 99%